Hambatan Yang Dialami Guru BK Untuk Melaksanakan Instrumen Non-Tes Dalam Pelayanan BK Dan Usaha Mengatasinya - Rina Suryani; Azrul Said; Indah Sukmawati (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2019)
Guidance and counseling teachers assignment in school is to provide optimum service according to the needs of students. Non-test instrument is one of the types of support activities to reveal the condition of the students as they are. This research is aimed to describe internal and external obstruction from the self and effort by guidance and counseling teachers to overcome obstruction to will do non-test instruments in the guidance and counseling service in school. This research is classified into quantitative research in descriptive type. This research sample are 26 guidance and counseling teachers of Junior High School in Padang city accredited A. The research instrument is questionnaire. The findings of the research revealed: the implementation of the non-test instruments have not been fully, because internal and external obstruction from the self  guidance and counseling teacher and the average guidance and counseling teachers has tried to overcome these obstruction.